A new species of bagrid catfish genus Tachysurus (Teleostei: Bagridae) from Wu river basin in central Taiwan - Chen, I-Shiung; Liu, Jian-Chin; Yeh, Ming-Fon (Zootaxa, 2024)
A new species of freshwater bagrid catfishes, Tachysurus (Teleostei: Bagridae) were collected from Wu river basin in central Taiwan. The new species, Tachysurus flumendraco n. sp. is most similar to Taiwanese endemic, T. adiposalis (Oshima, 1919) than any other congeneric species in eastern Asia. It can be well distinguished by the following unique combination of features: (1) dorsal fin rays II + 8; (2) anal fin rays: modally 3 + 18 = 21; (3) spine of pectoral fin with posterior serrations modally 18; (4) vertebral count usually 5 + 43–44; and (5) specific coloration pattern: body and head entirely bright creamy yellow to golden yellow, dorsal half of head and trunk with light brown; all 4 pairs of barbels creamy white to snow white; adipose fin creamy yellow to brownish yellow; anal fin creamy yellow with lighter basal skin; and caudal fin creamy yellow with distal black margin. The brief morphological comparison with close related species would be also addressed.